2016
DOI: 10.3390/nu8110673
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Eating Behaviors and Food Addiction among Nutrition Major College Students

Abstract: Evidence of whether nutrition students are free from food-related issues or at higher risk for eating disorders is inconsistent. This study aimed to assess disordered eating behaviors and food addiction among nutrition and non-nutrition major college students. Students (n = 967, ages 18–25, female 72.7%, white 74.8%) enrolled at a public university completed online demographic characteristics surveys and validated questionnaires measuring specific disordered eating behaviors. Academic major category difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
78
4
9

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(103 citation statements)
references
References 57 publications
12
78
4
9
Order By: Relevance
“…Only one study was identified with a high proportion of males (92%, in a veteran study) (62) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) .…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…Only one study was identified with a high proportion of males (92%, in a veteran study) (62) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) . Other groups included bariatric weight-loss groups (n = 6) (15,22,37,56,61,65) , undergraduate/students (n = 7 studies) (5,35,68,71,74,80,81) and disordered eating groups (n = 7) (17,43,47,49,50,64,73) .…”
Section: Description Of Included Studiesmentioning
confidence: 99%
“…It is possible that the differences in prevalence seen here are related to the different version of the YFAS applied. A potentially interesting difference between the prevalence of FA found by Yu and colleagues [19] as compared to that reported by Murphy and associates [7] is the platform used for data collection. Murphy and associates [7] collected data using a pencil and paper technique while Yu and colleagues [19] utilized an on-line platform.…”
Section: Discussionmentioning
confidence: 90%
“…A potentially interesting difference between the prevalence of FA found by Yu and colleagues [19] as compared to that reported by Murphy and associates [7] is the platform used for data collection. Murphy and associates [7] collected data using a pencil and paper technique while Yu and colleagues [19] utilized an on-line platform. Since the results presented here are more consistent with those described by Yu et al [19], it seems that the data collection platform used is important to consider when interpreting results.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations